2002
DOI: 10.1074/jbc.m204888200
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-x Complements Saccharomyces cerevisiae Genes That Facilitate the Switch from Glycolytic to Oxidative Metabolism

Abstract: All eukaryotic organisms have mechanisms to adapt to changing metabolic conditions. The mammalian cell survival gene Bcl-x L enables cells to adapt to changes in cellular metabolism. To identify genes whose function can be substituted by Bcl-x L in a unicellular eukaryote, a genetic screen was performed using the yeast Saccharomyces cerevisiae. S. cerevisiae grows by anaerobic glycolysis when glucose is available, switching to oxidative phosphorylation when carbohydrate in the media becomes limiting (diauxic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
53
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 35 publications
5
53
0
Order By: Relevance
“…Studies in yeast suggest that Bcl-x L expression may promote mitochondrial physiology by allowing for continued oxidative phosphorylation and maintenance of cellular ATP levels despite events such as decreased glycolysis (12). The greater expression of Bcl-x L during the hibernation season strengthens our hypothesis that the intestine of hibernating squirrels responds to stress stimuli that might lead to cell death by increased expression of anti-apoptotic pathways.…”
Section: Aim 2 Consequences Of Oxidative Stress In the Intestine Dursupporting
confidence: 67%
“…Studies in yeast suggest that Bcl-x L expression may promote mitochondrial physiology by allowing for continued oxidative phosphorylation and maintenance of cellular ATP levels despite events such as decreased glycolysis (12). The greater expression of Bcl-x L during the hibernation season strengthens our hypothesis that the intestine of hibernating squirrels responds to stress stimuli that might lead to cell death by increased expression of anti-apoptotic pathways.…”
Section: Aim 2 Consequences Of Oxidative Stress In the Intestine Dursupporting
confidence: 67%
“…It is possible that this mitochondrial function is regulated in response to cell growth, as prohibitin protein levels appear to increase in differentiated cells (Thompson et al, 2001). It has also been suggested that prohibitin may protect against apoptosis at times of metabolic stress in both yeast and mammalian cells, a function possibly related to its localization in the mitochondria (Vander Heiden et al, 2002). The cell-cycle function of prohibitin is less well understood and there is some dispute over the precise role of the protein (Coates et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…An SVF1-null strain marked with the HIS3 gene was generated in the wild-type parental strain by homologous replacement using methods previously described (Bahler et al 1998). In the W303 background, replacement of the coding region of SVF1 with the HIS3 and kanamycin resistance gene was performed as described (Bahler et al 1998;Vander Heiden et al 2002). All genomic deletions were confirmed by PCR to regions surrounding the deletion as well as phenotypic confirmation after tetrad dissection.…”
Section: Methodsmentioning
confidence: 99%
“…We identified SVF1 in a screen for yeast factors regulating cell survival that could be partially complemented by expression of mammalian Bcl-x L (Vander Heiden et al 2002). We have shown that while Svf1p and Bcl-x L have distinct functional properties, Svf1p functions to regulate survival under a variety of stress conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation